Computational Biology- Nano Programmed Carrier and Computed Aided Surgical for Cancer - Trivedi, Smith S (International Journal of Computer Sciences and Engineering, 2025)
The task of dealing with human body is one of the most complex one especially when it comes to curing someone suffering from heavy torment of malignant tumors. Cancer therapies are currently limited to surgery, radiation, and chemotherapy. All three methods risk damage to normal tissues or incomplete eradication of the cancer. Computational methods involves the development and application of data-analytical and theoretical methods, and computational techniques to the study of biological, and behavioral systems, and with Nanotechnology it offers the means to target chemotherapies directly and selectively to cancerous cells and neoplasms, guide in surgical resection of tumors, and enhance the therapeutic efficacy of radiation-based and other treatment modalities. All of this can add up to a decreased risk to the patient and an increased probability of survival. “Nano programmed carriers” or “NPC” carrying effective drugs are deployed in the blood stream. They are programmed to hit only the right spot through DNA computing which is interface to biochemical processes and are highly directional. On the other hand cancer abrupt can be predicted through Cancer computational biology. It aims to determine the future mutations in cancer through an algorithmic approach .It allows the gathering of data points using nano programmed robots and other sensing devices. This data is collected from DNA, RNA, and other biological structures. Areas of focus include determining the characteristics of tumors, analyzing molecules that are Involved in causing cancer, and understanding how the human genome relates to the causation of cancer